MENELUSURI JEJAK KEARIFAN LOKAL BUDAYA ETNIK JAWA DALAM LAPORAN KEUANGAN SEKTOR PUBLIK - Nareswari, Sita Histri (Universitas Muhammadiyah Kalimantan Timur, 2017)
Based on Agency Theory, as a form of the principal (government) accountability to the agency (citizens) over the management of resources, the government agency as a public sector organization must prepare a financial report. To avoid fraud in the accounting practice of financial statements, it is necessary to implementation the values in the financial statements that also derived from the Javanese ethnic culture as local wisdom in the preparation of financial statements. This article contains values in the financial statements derived from ethnic Javanese culture which is implemented in the preparation of financial statements as one of the accounting practices in the public sector. This research is a qualitative research using in depth interview complemented with literature study. The results revealed there are several values in the financial statements that are also contained in the value of ethnic Javanese culture both in Ancient Javanese Philosophy and Tembang Macapat. Values in the preparation of financial statements in accordance with piwulang in Javanese ethnic culture is Transparent and honest (in accordance with one stanza macapat work of Ranggawarsita in Fiber Kalatidha); Provide useful information (Urip Iku Urup); Prudential Principle (Alon-alon Waton Klakon).